1999
DOI: 10.3354/dao035013
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow trout leucocyte activity:influence on the ectoparasitic monogenean Gyrodactylus derjavini

Abstract: The ectoparasitic monogenean Gyrodactylus deqavinl from ralnbow trout Oncorhynchus mykiss was exposed in vltro to macrophages isolated as pentoneal exudate cells or as pronephros cells from the host Cells colonized the parasite especially in the mannose-nch regions in the c e p h a l~c ducts where ciliated structures were abundant Opsonizatlon wlth fresh serum, in contrast to heatinactivated serum, enhanced colonlzat~on also on other body parts The adverse effect of the activated macrophages towards G derjavln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 28 publications
(40 reference statements)
2
36
0
Order By: Relevance
“…Therefore, the basis for the response against gyrodactylids is not likely to be associated with immunoglobulin reactivity. Factors such as complement (Buchmann 1998, Buchmann and Bresciani 1999 have been demonstrated to affect the parasites substantially. If lectins present in fish skin (Buchmann 2001) has been demonstrated that G. derjavini elicits the expression of a number of immune relevant genes in rainbow trout skin (Lindenstrøm et al 2003(Lindenstrøm et al , 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the basis for the response against gyrodactylids is not likely to be associated with immunoglobulin reactivity. Factors such as complement (Buchmann 1998, Buchmann and Bresciani 1999 have been demonstrated to affect the parasites substantially. If lectins present in fish skin (Buchmann 2001) has been demonstrated that G. derjavini elicits the expression of a number of immune relevant genes in rainbow trout skin (Lindenstrøm et al 2003(Lindenstrøm et al , 2004.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that FCA can be used not only as a vaccine carrier but also as a stimulant of nonspecific immunity (Anderson 1992, Secombes 1994. The nonspecific immune factors including complement and leucocytes are known to negatively influence the establishment of gyrodactyids (Buchmann 1998, 1999, Harris et al 1998, Buchmann & Bresciani 1999. Buchmann & Bresciani (1999) reported that Gyrodactylus derjavini survived less than 3 h when exposed to supernatant from peritonea1 macrophages, which were considered to be activated by i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Hypersecretion of mucus [293][294][295][296][297] may be associated [296] or not [298] with a localized epithelial cell hyperplasia. Perhaps the hyperplasia is mediated by IL-1 released by activated macrophages [299]. Inflammation is the other cellular process implied in the parasite response in the fish skin.…”
Section: Fish Skin Mucosal Immunologymentioning
confidence: 99%